The Use of Speed Reading to Improve EFL Learners’ Reading Comprehension - Ortalisje, Dethan Erniani (Journal of Language, Education, Literature, and Culture, 2025)
The present study aimed to examine whether (a) students who participated in a speed reading course improved their reading speed more than those who did not, and (b) whether these students also achieved better comprehension. Thirty participants were divided into two groups: an experimental group and a control group. Data were collected using a test instrument. The experimental group received speed reading instruction, while the control group did not undergo any such intervention. The findings revealed that students who engaged in speed reading activities increased their average reading speed by 28 words per minute (23%) and improved their comprehension by 3.2 points. Additionally, the experimental group showed a significant improvement from pretest to posttest, whereas the control group demonstrated no notable difference between the two tests.